Social Skills and Academic Competence Among Senior High School Students: A Basis for Guidance Program - Blesselda Kaye Ruga (Research Synergy Foundation, 2024)
To improve the academic success of Filipino students by not relying solely on acquired knowledge, this study aimed to investigate the correlation between social skills and academic competence among senior high school students of Cabuyao Institute of Technology. Through the developed guidance program, schools could better understand the importance of social skills, enabling students to communicate more effectively and excel academically. A total of 236 randomly chosen senior high school students of the Cabuyao Institute of Technology participated by responding to the two adopted questionnaires. The model was then analyzed and evaluated using the Mean, H-Comp Scale, Social Skills Rating System, and Pearson-product Moment Correlation. The findings showed a strong correlation between social skills and academic competency. In addition, the participants demonstrated a high degree of social skills and a moderate to acceptable degree of academic competency. The “EQUIP Program” was developed to address problems and challenges observed from the results that prevent academic enablers from performing at their highest level and to support them in developing stronger interpersonal skills. This program focuses on Personal and Social Development, Academic Development, and Enhancement of Competencies.